Quantification of tumour hypoxia - Bussink, J. (Nuklearmedizin - NuclearMedicine, 2010)
Tumor cell hypoxia is considered one of the important causes for radiation resistance. The introduction of IMRT (intensity modulated radiotherapy) allows specific boosting of tumor subvolumes that may harbour these radioresistant tumour cells. PET imaging of these subvolumes can be incorporated into treatment planning.However, at this moment microenvironmental changes visualized and quantified by means of PET-imaging need to be validated by highresolution microscopic techniques. This will allow interpretation of imaging techniques with intermediate resolution (such as PET/CT) in relation to complex cellular signaling in response to anti-cancer treatments.
Keywords: Autoradiography; hypoxia; CAIX; head and neck cancer; xenografts